2017
DOI: 10.1111/1365-2435.13009
|View full text |Cite
|
Sign up to set email alerts
|

Water restriction causes an intergenerational trade‐off and delayed mother–offspring conflict in a viviparous lizard

Abstract: Parenting is costly and because the relationship between the mother and embryos is not mutualistic, mother–offspring conflicts may exist whenever resource are scarce. However, intergenerational trade‐offs and conflicts resulting from limited access to water, a vital and depreciable resource, remain largely overlooked. In this study, we examined the physiological, reproductive and life‐history responses to water restriction in the European Common Lizard (Zootoca vivipara). We hypothesized that, under water‐limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 69 publications
(143 reference statements)
7
43
0
Order By: Relevance
“…identified with a unique toe clip code and maintained in conditions as previously described (Dupoué et al, 2018). identified with a unique toe clip code and maintained in conditions as previously described (Dupoué et al, 2018).…”
Section: Species 1: the Asp Vipermentioning
confidence: 99%
See 3 more Smart Citations
“…identified with a unique toe clip code and maintained in conditions as previously described (Dupoué et al, 2018). identified with a unique toe clip code and maintained in conditions as previously described (Dupoué et al, 2018).…”
Section: Species 1: the Asp Vipermentioning
confidence: 99%
“…Maternal effort during gestation is thus mainly oriented to hormone or salt exchange with embryos, regulation of water supply, and thermoregulation (Dupoué et al, 2018;Le Galliard, Bris, & Clobert, 2003;Lourdais, Lorioux, Dupoué, Wright, & DeNardo, 2015). Maternal effort during gestation is thus mainly oriented to hormone or salt exchange with embryos, regulation of water supply, and thermoregulation (Dupoué et al, 2018;Le Galliard, Bris, & Clobert, 2003;Lourdais, Lorioux, Dupoué, Wright, & DeNardo, 2015).…”
Section: Ta B L Ementioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we have shown that common lizards exposed to dry soil conditions invest more in exploration behaviors (Rozen‐Rechels et al ), and juvenile lizards living in dry habitats disperse more from their natal home range (Massot et al ), whereas sub‐adults reduce their locomotor activity during a chronic water restriction (Lorenzon et al ). Here, we repeatedly measured daily patterns of individual activity and microhabitat selection as well as body temperature and thermoregulation accuracy during one week in adult individuals, gravid females and males, exposed to a chronic water restriction (Dupoué et al ) compared to individuals having access to water ad libitum. To quantify potential interactions between water deprivation and heat stress, we implemented a mid‐day heat stress every two days.…”
Section: Introductionmentioning
confidence: 99%